2014
DOI: 10.1039/c3ay41626g
|View full text |Cite
|
Sign up to set email alerts
|

Enantiomeric separation of sitagliptin by a validated chiral liquid chromatographic method

Abstract: An enantioselective reversed phase high performance liquid chromatographic method was developed and validated. The enantiomers of sitagliptin were resolved on a Chiralcel OD-RH (150 mm  4.6 mm, 5 mm) column using a mobile phase system containing 3 M potassium di-hydrogen phosphate buffer (pH 4.0)methanol-acetonitrile (60 : 30 : 10, v/v/v). The resolution between the enantiomers was not less than 3.0. The pH value of buffer solution in the mobile phase played a key role in enhancing chromatographic efficiency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Under these conditions, the peak shapes of both S-and R-sitagliptin enantiomers appeared to be symmetrical and resolution factor was at least 4.0 (Reddy et al, 2013). Recently, Ramesh et al (2014) reported an enatioselective LC-MS/MS method for quantitative determination of undesired (S)-sitagliptin from sitagliptin in bulk drugs. Both the enantiomers' resolutions were ≥3.0 and this was achieved on Chiracel OD-RH column using an isocratic mobile phase (3 M potassium dihydrogen phosphate-MeOH-water, 60:30:10, v/v/v) within 10 min run time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under these conditions, the peak shapes of both S-and R-sitagliptin enantiomers appeared to be symmetrical and resolution factor was at least 4.0 (Reddy et al, 2013). Recently, Ramesh et al (2014) reported an enatioselective LC-MS/MS method for quantitative determination of undesired (S)-sitagliptin from sitagliptin in bulk drugs. Both the enantiomers' resolutions were ≥3.0 and this was achieved on Chiracel OD-RH column using an isocratic mobile phase (3 M potassium dihydrogen phosphate-MeOH-water, 60:30:10, v/v/v) within 10 min run time.…”
Section: Discussionmentioning
confidence: 99%
“…Among these columns only Chiralpak AD-RH and Chiralcel OJ-RH gave the required selectivity between sitagliptin and undesired impurity. Based on further optimization of mobile phase composition and baseline separation of the two peaks, Chiracel OD-RH was chosen for method validation purposes (Ramesh et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Enantiomers of drugs often differ in their pharmacological action. Other gliptins such as linagliptin,[ 10 ] alogliptin,[ 11 ] and sitagliptin[ 12 ] and teneligliptin also show chirality. However, with the exception of teneligliptin—all the other gliptins are manufactured by a single company.…”
Section: Drug Quality—things To Considermentioning
confidence: 99%
“…Sitagliptin analysis also has been reported with its degradation product and metformin using HPLC 8 , with its N-acetyl impurity, metformin and metformin related impurities using UPLC 9 . So far there are only two published direct enantiomeric separation methods using AD-H column 10 , an OD-RH column 11 and an indirect method 12 .…”
Section: Figure 1: Structure Of (R)-sitagliptinmentioning
confidence: 99%